2020
DOI: 10.17219/acem/111812
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic equivalency of mobile CTG devices and remote analysis to conventional on-site nonstress test

Abstract: Background.Remote pregnancy monitoring is one of the most promising applications of telemedicine; however, the diagnostic value of self-examination using mobile cardiotocography (CTG) devices and remote analysis of the subsequent results has never been properly studied.Objectives. The study aimed to compare the diagnostic usefulness of CTG self-examination using a mobile device to examination performed by a medical professional using a stationary device; and to evaluate the quality of CTG analysis performed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…In recent years, with the full liberalization of the national second-child policy and the gradual increase of elderly pregnant women, the work pressure of the hospital's fetal heart rate monitoring department has also increased [1]. How to find a way that is convenient and guarantees the health and safety of pregnant women and the service diagnosis and treatment model to reduce the pressure of the fetal heart care unit in the hospital is a hot issue that everyone is concerned about.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the full liberalization of the national second-child policy and the gradual increase of elderly pregnant women, the work pressure of the hospital's fetal heart rate monitoring department has also increased [1]. How to find a way that is convenient and guarantees the health and safety of pregnant women and the service diagnosis and treatment model to reduce the pressure of the fetal heart care unit in the hospital is a hot issue that everyone is concerned about.…”
Section: Introductionmentioning
confidence: 99%
“…Systems enabling women to monitor FHR and UC at home have been built in the last years, and several studies show that their quality is close to the quality of high‐grade cardiotocographs used in hospitals 62 . A qualitative study run by Van den Heuvel et al concluded that home‐based telemonitoring of fetal parameters could be of great use for high risk pregnancies, 63 and another study by Pilarczyk et al concluded that it should be implemented into everyday obstetric care 64 . As remote CTG monitoring may be performed without any medical practitioner around, the integration of computerized CTG analysis in the process will be particularly useful.…”
Section: Discussionmentioning
confidence: 99%
“…The application of telemedicine in obstetrics can be categorized by the services provided (educational, teleconsultations, and remote monitoring) or by the problem addressed (lifestyle issues, maternal complications, and fetal complications). Remote pregnancy monitoring is one of the most promising applications of telemedicine, and our study categorized it as “remote monitoring for fetal complications.” 11 Several investigators have evaluated the efficacy and safety of home care management in obstetrics and demonstrated the safety of high‐risk pregnancies (including FGR). However, the evidence for this is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges with the management of patient burden exist in areas where obstetric facilities are limited, and, in high‐risk pregnancies, such as those with FGR, the use of iCTG would reduce the number of visits. Telemedicine can also improve access to medical services in rural and underdeveloped countries where the concentration of health centers is sparse 11 . In particular, our health facility is less easily accessible and may require 90 min of commute time for some patients.…”
Section: Discussionmentioning
confidence: 99%